The degree to which seventh grade students possess grammatical skills (Journal of Hama University, 2025)
This study aimed to measure the degree to which seventh grade students possess grammatical skills. To achieve the objectives of the study, a sample consisting of (50) students was selected. The researcher used the descriptive analytical method. The study tool, represented by a list of grammatical skills appropriate for the seventh grade, was used, in addition to an achievement test. The results of the study revealed that there was a general weakness among students in grammatical skills as a whole, as the percentage of their possession of grammatical skills reached (29%), in addition to students’ weakness in sub-grammatical skills, where the percentage ranged between (16%) and (34%), which is a low percentageIn view of the research into many proposals, the most important of which are: conducting evaluation studies of grammatical skills in the Arabic language curriculum at the basic education stage, envisioning preparation for a unit that needs to develop students’ grammatical skills.
Keywords: Grammatical skills, possession, basic education stage